The Influence of Total Quality Management (TQM) and Characteristics of Management Accountig Information Systems on Managerial Performance - Tamy Ali Januarty; Siti Asyiah Sundari (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Managerial performance is one of the things that can drive the success of a company's goals. There are several things that can affect and improve managerial performance including total quality management and management accounting information systems. The application of total quality management will help the managerial role to further improve its performance so that it can be carried out properly. In addition, the existence of an available management accounting information system will support the control and decision-making process of a manager. This study aims to determine the effect of total quality management and the characteristics of management accounting information systems on managerial performance at PT. So Good Food Jakarta Branch. Application of total quality management and management accounting information systems at PT. The So Good Food Jakarta Branch has been running and is well available, but there needs to be improvement so that the implementation of total quality management and management accounting information systems can run optimally. The method in this study was to conduct a questionnaire survey with an ordinal scale form to 40 respondents from PT. So Good Food Jakarta Branch, then data processing is carried out using SEM-PLS data analysis techniques and is designed with a quantitative approach to descriptive analysis and verification. The results of this study are expected to be a solution to problems related to managerial performance at PT. So Good Food Jakarta Branch. The results of this study prove that: (1) total quality management has an effect on managerial performance, (2) the characteristics of management accounting information systems have an effect on managerial performance